Performance differences in Division III female field hockey athletes with prior lower extremity injuries over a competitive season - Feliciano, J.; McNally, M. P.; Busch, A. M. (The Sport Journal, 2020)
Background: In the sport of field hockey, athletes encounter repetitive unilateral movements due to the nature of the sport, possibly leading to detectable changes in performance variables or functional movements.